2021
DOI: 10.3389/fnut.2021.734267
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise on Appetite in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Background: The effect of physical activity and exercise on hunger and satiety has been well-studied in younger adults, but the influence of aging is less understood. While some evidence suggests that acute bouts of exercise induce a compensatory eating drive, long-term activity may improve satiety sensitivity. The objective of this study was to investigate the effects of exercise on appetite in older adults.Methods: We systematically reviewed available literature investigating the effect of exercise on appeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…On the other hand, although physical activity was not associated with the occurrence of undernutrition after adjusting for BMI, there is still a possibility that physical activity before the disaster may work to prevent undernutrition. A systematic review found that physical activity promotes appetite control and balanced energy intake [ 30 ]. It also reports that physical activity is the least expensive day drug therapy because enhanced physical activity lowers the depression risk and shows a preventive effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although physical activity was not associated with the occurrence of undernutrition after adjusting for BMI, there is still a possibility that physical activity before the disaster may work to prevent undernutrition. A systematic review found that physical activity promotes appetite control and balanced energy intake [ 30 ]. It also reports that physical activity is the least expensive day drug therapy because enhanced physical activity lowers the depression risk and shows a preventive effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut dysbiosis, the imbalance of gut microbiota, affects nutrition absorption in the entericus and causes malnutrition to some extent ( 58 , 59 ). Increased daily activities or physical exercises improve the appetite, which may reduce the risk of sarcopenia ( 60 , 61 ). Moreover, exercises can trigger gut microbiota secreting short-chain fatty acids with anti-inflammatory effects, reduce oxidative stress, and maintain muscle mass ( 62 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may eventually lead to phenotypic outcomes such as weight loss and loss of muscle mass (37) , while it has been argued that PA has the potential to modulate resting hunger and satiety in the older population and may benefit the older population by promoting EBRB. However, increased lean body mass and RMR have been observed but may not necessarily be associated with increased energy intake (38)(39)(40) . The association between a healthy or high-quality diet and PA could be explained by the participants' socio-economic status and living status (41,42) .…”
Section: Discussionmentioning
confidence: 99%